Analisis Pengaruh Opini Audit Tahun Sebelumnya, Debt Default, dan Opinion Shopping Terhadap Penerimaan Opini Audit Going Concern Pada Perusahaan Manufaktur Tahun 2015-2019 - Rachman, Ilma Huda; Subaki, Achmad; Rito, Rito (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This research aims to determine how the effect of the previous year's audit opinion, debt default, and opinion shopping on going concern audit opinion in manufacturing companies listed on the IndonesiaStock Exchange in 2015-2019. The sample used in this study were 12 manufacturing companies Thesample selection technique used was purposive sampling and the collection technique used in this studywas explanation. The results of this study indicate that the previous year's audit opinion has an effect ongoing concern audit opinion, debt default affects the going concern audit opinion, and opinion shoppinghas no effect on going concern audit opinion.